PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABLE MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar Di BEI Periode 2017-2029) - , Rofika, Dwi Fatimah , Zirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the Effect of Profitability and Leverage on Tax Avoidance with Corporate Social Responsibility (CSR) Disclosures as Moderating Variables in Manufacturing Companies Listed on the IDX in 2017-2019. The population in this study were all manufacturing companies listed on the IDX in 2017-2019. The sample selection in this study used purposive sampling method. This study uses a sample of 24 manufacturing companies listed on the IDX. The results showed that profitability had an effect on Tax Avoidance. Leverage has an effect on Tax Avoidance. Corporate Social Responsibility can moderate the effect of profitability on Tax Avoidance. And Corporate Social Responsibility can moderate Leverage on Tax Avoidance. Keywords: Profitability, Leverage, Tax Avoidance and Corporate Social Responsibility (CSR)